A Comparative Study of RME and PBL Models on Students’ Problem-Solving Skills Based on Mathematical Communication - Marindra Kariadi; Edy Waluyo; Shahibul Ahyan (Program Studi Pendidikan Matematika FKIP Universitas Pattimura, 2025)
This study aims to compare the effects of the Realistic Mathematics Education (RME) and Problem-Based Learning (PBL) models on junior high school students’ problem-solving skills, viewed through the lens of mathematical communication. A quasi-experimental method employing a 2×2 factorial design (treatment by level) was implemented. The sample consisted of 32 seventh-grade students from a public junior high school in East Lombok, West Nusa Tenggara, divided into four groups based on instructional model and mathematical communication level (high vs. low). The research instrument was an essay-based test administered both before and after the intervention. Two-way ANOVA results revealed a statistically significant effect of the learning model on problem-solving skills (F = 106.68; p < 0.001), a significant effect of mathematical communication level (F = 85.34; p < 0.001), and a significant interaction between the two factors (F = 13.00; p = 0.0012). Dunnett’s post hoc analysis indicated that students with both high and low levels of mathematical communication performed significantly better under the RME model than under PBL (t = 3.56 and t = 3.74, respectively; t₀.₀₅ = 2.49). These findings suggest that RME is more effective than PBL in enhancing students’ problem-solving abilities, regardless of their level of mathematical communication, and is well-suited for implementation in diverse classroom settings.